Analisis Portofolio Optimal CAPM dan Single Index Model pada Perusahaan IDX30 - Muhammad Wafa Aunillah; Wahyudi Wahyudi (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study is to analyze the optimal stock portfolio using the Capital Asset Pricing Model and Single Index Model, then look at the portfolio performance formed on IDX30 stocks for the period February 2017 – July 2021 with a sample of 16 stocks. This research includes quantitative descriptive. The results showed: (1) CAPM method, obtained 2 stocks, namely: BBCA and ICBP. With a portfolio return rate of 0.26%, and a portfolio risk level of 5.32%. (2) SIM method, only one share is obtained, namely: BBCA. With a portfolio return rate of 1.38%, and a portfolio risk level of 0.57%. (3) the performance of the CAPM portfolio is worth 0.0485 Sharpe index, 0.0034 Treynor, and 0.00515 Jensen. (4) SIM portfolio performance has an index of Sharpe 2.4280, Treynor 0.0154, and Jensen 0.01690. (5) stock performance in CAPM, namely BBCA and ICBP with Sharpe indexes 1.09286 and 0.17500, Treynor 0.00342 and 0.00319, and Jensen 0.00615 and 0.00116. (6) stock performance on SIM, namely BBCA with Sharpe index of 0.07857, Treynor 0.00025, and Jensen 0.00331